Nikolay Mikhajlovich Bеlajev (1890-1944) as mentor - N. L. Belevcova; I. S. Yavorska (History of science and technology, 2013)
The article is devoted to the analysis of pedagogical activity of Nikolay Mikhajlovich Beliaieva, prominent domestic mathematician, specialist in industry of structural mechanics, theory of resiliency and resistance of materials, member-correspondent of Academy of sciences of the USSR.